2023
DOI: 10.3389/fendo.2023.1142644
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the cardiovascular effects of IGF-1

Abstract: IntroductionCardiovascular (CV) disorders are steadily increasing, making them the world’s most prevalent health issue. New research highlights the importance of insulin-like growth factor 1 (IGF-1) for maintaining CV healthMethodsWe searched PubMed and MEDLINE for English and non-English articles with English abstracts published between 1957 (when the first report on IGF-1 identification was published) and 2022. The top search terms were: IGF-1, cardiovascular disease, IGF-1 receptors, IGF-1 and microRNAs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 223 publications
0
19
0
Order By: Relevance
“…Additionally, AF can be an intractable dysrhythmia, so identifying the gene–environment interactions underlying this disease may uncover novel therapeutic strategies to better reverse the underlying pathogenesis. In particular, in these context, drugs and bioactive molecules, exerts their beneficial effects via epigenetic regulations 67–69 . Our findings further underscore the exciting potential of novel ‘epidrugs’ targeting the methylation‐sensitive underpinnings of AF.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Additionally, AF can be an intractable dysrhythmia, so identifying the gene–environment interactions underlying this disease may uncover novel therapeutic strategies to better reverse the underlying pathogenesis. In particular, in these context, drugs and bioactive molecules, exerts their beneficial effects via epigenetic regulations 67–69 . Our findings further underscore the exciting potential of novel ‘epidrugs’ targeting the methylation‐sensitive underpinnings of AF.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, in these context, drugs and bioactive molecules, exerts their beneficial effects via epigenetic regulations. [67][68][69] Our findings further underscore the exciting potential of novel 'epidrugs' targeting the methylation-sensitive underpinnings of AF.…”
Section: Discussionmentioning
confidence: 61%
“…Increased circulating IGF-1 in plasma reduces the risk of hypertension in women aged 30–55 [ 19 ]. Low serum IGF-1 levels predict the development of early cardiovascular disorders and hypertension [ 20 ]. The above data were based on experimental models or studies in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The level of IGF-1 is regulated by many factors (insulin resistance, insulin levels, lipids, vitamin D3, hormones, metabolic syndrome, and inflammatory parameters) [ 20 , 21 , 22 , 23 , 24 ]. IGF-1 concentration in the upper reference range is associated with reduced blood pressure and vascular tone [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 promotes heart development, increases cardiac output, stroke volume, contractility, and ejection fraction. Human studies have also shown that low levels of serum free or total IGF-1 are associated with an increased risk of cardiovascular and cerebrovascular diseases ( 9 ). The role of IGF-1 in the body is becoming increasingly apparent.…”
Section: Introductionmentioning
confidence: 99%